Correlation of competitive exercises technique with biomechanical structure of barbell displacement in weightlifting - Oleshko, V.; Dekha, V.; Yang, T.; Slobodianyuk, V. (Journal of Physical Education and Sport, 2020)
The study outlines comparative characteristics for biomechanical structure of barbell displacement during the snatch as well as the first stage of the clean and jerk among males and females of elite group that have different body weight in two main phases. These phases of barbell displacement are called as follows: the amplitude of barbell departure in final acceleration phase and the magnitude of its displacement into supporting squat phase, because they characterise economical efficiency of technique, applied in performing competitive exercises. ?urpose of the article is to determine economical efficiency of technique, applied in performing competitive exercises by weightlifters of different genders that have different body weight, with the help of biomechanical structure of barbell displacement. Material and methods include analysis of literature, video recording ofcompetitive exercises, biomechanical analysis, as well as mathematical statistics. Results. We have determined amplitude value of barbell departure in the phase of final acceleration and the magnitude of barbell displacement into supporting squat with the help of biomechanical structure of barbell displacement by weightlifters of different genders that have different body weight. This allows evaluating economical efficiency of the snatch and clean and jerk technique in the process of improving their sportsmanship. Conclusions. Biomechanical structure of barbell displacement in final acceleration phase and supporting squat has some differences depending on competitive exercise, gender of athletes and their belonging to the group of weight categories.